2012
DOI: 10.1021/jp209259j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical–Experimental Study of Formic Acid Photofragmentation in the Valence Region

Abstract: Photoionization and photofragmentation studies of formic acid (HCOOH) are performed for the valence shell electron ionization process. The total and partial ion yield of gaseous HCOOH were collected as a function of photon energy in the ultraviolet region, between 11.12 and 19.57 eV. Measurements of the total and partial ion yield of gaseous formic acid molecule are performed with a time-of-flight mass spectrometer at the Synchrotron Light Brazilian Laboratory. Density functional theory and time dependent dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 54 publications
(98 reference statements)
4
22
0
Order By: Relevance
“…1,10,11,16,17 The explanation found in the literature for these cations is generally due to the presence of the isotope 13 C. In a brief analysis by Leach et al 16 for the case of acetic acid, m/q = 60, it is suggested that the appearance of the ion at m/q = 61 can be due to the presence of an isotope 13 C, to the molecular fragmentation of dimers, or to the fragmentation of a complex formed by water contamination. According to this work, the formation energy of a protonated ion from a dimer would be about 200 meV lower than the ion derived from monomers containing 13 Aim of the present work is to analyze the process of protonation due to the formation of dimers and their influence on the results of molecular ionization and fragmentation pattern at VUV range.…”
mentioning
confidence: 99%
“…1,10,11,16,17 The explanation found in the literature for these cations is generally due to the presence of the isotope 13 C. In a brief analysis by Leach et al 16 for the case of acetic acid, m/q = 60, it is suggested that the appearance of the ion at m/q = 61 can be due to the presence of an isotope 13 C, to the molecular fragmentation of dimers, or to the fragmentation of a complex formed by water contamination. According to this work, the formation energy of a protonated ion from a dimer would be about 200 meV lower than the ion derived from monomers containing 13 Aim of the present work is to analyze the process of protonation due to the formation of dimers and their influence on the results of molecular ionization and fragmentation pattern at VUV range.…”
mentioning
confidence: 99%
“…Threshold photoelectron and photoionization total ion yield spectra were reported by Siggel-King et al in the 11–21 eV range. Finally, the total ion yield and partial ion yield in the range of 12.12–19.57 eV were reported by Arruda et al These authors also report density functional and time-dependent density functional calculations of the ground- and excited-state electronic energies of neutral and ionic formic acid as well as their fragments. Previous theoretical studies also include the investigation of the ionic states observed in the photoelectron spectrum by Takeshita and the calculated VUV absorption spectrum reported by Osted et al…”
Section: Introductionmentioning
confidence: 66%
“…DeWitt [27] have addressed the dependence of dissociation yield with molecular size, however until the present, Keldysh theory is applied. More than 20 different cations were observed corresponding to some dissociation channels already proposed [22]. Spectra were obtained at radiation intensities between 9.25×10 9 and 5×10 10 W/cm 2 , without and with He and Ar as carrier gases.…”
Section: Resultsmentioning
confidence: 95%
“…Most of the ionic species have been observed in experiments of formic acid destruction by soft X rays [21,22] inner shell excitation [23] ultraviolet region [10] or the interaction with protons or electrons [19,28]. In this work, we analyze the mass spectra of the ions obtained as a result of the interaction between formic acid and laser radiation with different intensities of 532 nm radiation, contrasting them with some of the available theoretical and computational results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation